Assessing the Impact of the Budget Deficit on The Investment Potential of Public-Private pArtnerships in the EU Countries - Sergiienko, Larysa; Сергієнко, Ларіса; Bondarchuk, Nataliia; Бондарчук, Наталія Володимирівна; Belinska, Svitlana; Белінська, Світлана; Topolenko, Nadiia; Тополенко, Надія; Dziuba, Roman; Дзюба, Роман (ТОВ "ФІНТЕХАЛЬЯНС", 2025)
The investigation is aimed at identifying the relationship between the scale of the budget deficit and the investment potential of the public-private partnership in France and Italy over the period 2020–2023. The investment potential was reflected by two indicators: the direct investment in the public-private partnership project (billions of euros) and the number of projects that have reached financial closure. As a key explanatory change, the magnitude of the sovereign finance deficit per unit in billions of euros is shown, which ensures a stable interpretation of “a larger deficit means a larger quantity; there are billions of resources”. Linear regression with fixed edge effects is methodically designed, which makes it possible to strengthen the steel institutional background from internal conflicts and estimate the marginal influx of an additional one billion Euro deficit to show public-private partnership. To increase reliability, robust standard ablation using the Huber-White approach was used, and duplicate assessments of the skin edge were also performed. Descriptive statistics and correlation analysis are useful as an indicative addition to the causal interpretation of regression coefficients. The results show that the public-private partnership project faces significant challenges in relation to the scale of the deficit in order to attract investments. At the same time, for a number of projects, a stable and statistically variable effect was not revealed: the influx of deficit into the market is close to zero or non-existent. A practical interpretation emphasizes the need to reduce the deficit or, moreover, to protect long-term debts between public-private partnerships in the form of a short-term fiscal squeeze, which is the policy direction for a larger investment scale of public-private partnerships. Дослідження спрямоване на виявлення того, чи пов’язаний масштаб бюджетного дефіциту з інвестиційним потенціалом державно-приватного партнерства у Франції та Італії протягом 2020–2023 років. Інвестиційний потенціал вимірювали двома показниками: річним обсягом інвестицій у проєкти державно-приватного партнерства (мільярди євро) та кількістю проєктів, що досягли фінансового закриття. Як ключову пояснювальну змінну використано величину дефіциту державних фінансів за модулем у мільярдах євро, що забезпечує стабільну інтерпретацію «більший дефіцит означає більшу кількість мільярдів нестачі ресурсів». Методично застосовано лінійну регресію з фіксованими ефектами країн, яка дає змогу відокремити стале інституційне тло від внутрішньорічних коливань та оцінити граничний вплив додаткового одного мільярда євро дефіциту на показники державно-приватного партнерства. Для підвищення надійності використано робастні стандартні похибки за підходом Губера–Вайта, а також проведено дублюючі оцінювання окремо для кожної країни. Описові статистики й кореляційний аналіз використано як індикативне доповнення до причиново-наслідкової інтерпретації регресійних коефіцієнтів. Результати свідчать, що для обсягу інвестицій у проєкти державно-приватного партнерства спостерігається від’ємний нахил щодо масштабу дефіциту. Водночас для кількості проєктів стабільного та статистично переконливого ефекту не виявлено: вплив дефіциту на рахунок угод є близьким до нульового або несуттєвим. Практична інтерпретація підкреслює необхідність обмеження дефіциту або принаймні захисту довгострокових зобов’язань у межах державно-приватного партнерства від короткострокового фіскального тиску, якщо мета політики полягає в збільшенні саме інвестиційного масштабу державно-приватного партнерства.
Оцінювання впливу бюджетного дефіциту на інвестиційний потенціал державно-приватного партнерства в країнах ЄС
Keywords: budget deficit; бюджетний дефіцит; investment potential; інвестиційний потенціал; government-private partnership; державно-приватне партнерство; investments; інвестиції; number of projects; кількість проєктів; fixed effects; фіксовані ефекти; regression analysis; регресійний аналіз; fiscal policy; фіскальна політика; EU countries; країни ЄС